Doomscrolling Scale: its Association with Personality Traits, Psychological Distress, Social Media Use, and Wellbeing - Satici, Seydi Ahmet; Tekin, Emine Gocet; Deniz, M. Engin; Satici, Begum (SPRINGER, 2023)
Doomscrolling is a fairly new concept in mental health research which has attracted significant attention in recent years. This paper consists of three separate studies examining doomscrolling. In Study I (N = 378), both 15-item and 4-item forms of Doomscrolling Scale (DS) were confirmed by confirmatory factor analysis. Item Response Analysis demonstrated that all items had strong discriminative power. Different reliability coefficients supported the high reliability of DS. In Study II (N = 419), both correlation and network analysis indicated that doomscrolling was significantly associated with big five personality traits, social media addiction, fear of missing out, and some features of social media usage. In Study III (N = 460), the relationship of doomscrolling with psychological distress and wellbeing indicators -life satisfaction, mental well-being and harmony in life- were investigated. Structural equation modeling indicated that the relationship between doomscrolling and wellbeing indicators were mediated by psychological distress. This comprehensive and pioneering study on doomscrolling has highlighted the individual and social impacts of doomscrolling.
Keywords: Doomscrolling; Personality; Social media usage; FOMO; Wellbeing; Psychological distress; ANXIETY; DEPRESSION; VERSION; Social Sciences - Other Topics